ROLE OF FINE NEEDLE ASPIRATION CYTOLOGY IN THE EVALUATION OF THE SPECTRUM OF LYMPH NODE LESIONS. - DR. PAVITHRA. P; DR. GEETHA. J. P (International Journal of Pharma and Bio Sciences, 2014)
Fine needle aspiration cytology (FNAC) is a reliable and an inexpensive method for diagnosis of palpable masses at various sites. FNAC was performed on 319 patients with palpable lymphadenopathy over a period of three years. Ziehl Neelson staining was done wherever required. Clinicocytological correlation was done. FNAC diagnosis was found to be as follows: tubercular lymphadenitis in 135 cases (42.31%) followed by metastatic carcinoma in 64 (20.06%), reactive hyperplasia in 56 (17.55%), granulomatous lymphadenitis in 37 (11.59%), suppurative granulomatous in 10 (3.13%), suppurative lymphadenitis in 6 (1.88%) and lymphoma in 5 (1.56%). Aspirates were inadequate in 6 (1.88%) cases. FNAC is a useful and reliable tool in diagnosing non neoplastic and neoplastic lesions of lymph nodes and helps in making a wise decision in further management of patients as reactive and tubercular lymphadenitis can be treated conservatively while surgery might be required for malignant cases.